Analysis of the Impact on Axial Compression and Diametric tensile strength of concrete using recycled fine aggregate - Silva, Eduardo Dalla Costa; Marcelin, Dykenlove; Torres, Douglas Guedes Batista; Guerra, Thiago (International Journal of Advanced Engineering Research and Science, 2021)
Due to the current environmental crisis and the improper disposal of construction and demolition waste (CDW), the incorporation of these as aggregates in the manufacture of concrete is presented as one of the main alternatives for the proper disposal and consequent recycling of it. Such use requires technical knowledge regarding possible changes in the properties of the final product. Thus, this study aims to compare some of the main properties of conventional concrete with the executed one through the incorporation of recycled fine aggregates (RFA).The aggregate was collected in the recycling factory at FUTURE, a company located in Cascavel, Paraná – Brazil. Four mix ratios were elaborated, distinct by the replacement percentages of the conventional fine aggregate to the recycled one (0, 20, 40 e 60%), where the workability, the water absorption of the concrete, the axial compressive and tensile strength were evaluated. Thus, the increase of the workability and the absorption were verified with the highest degree of replacement as well as the reduction of the axial compressive and tensile strengths.